PENGARUH PENGUASAAN KOSAKATA DAN TEKNIK DEBAT TERHADAP HASIL BELAJAR BERBICARA MAHASISWA STKIP KUSUMA NEGARA JAKARTA: (An Experimental study at STKIP Kusuma Negara Jakarta) - -, megawati - (English Education:Journal of English Teaching and Research, 2018)
Abstract: The purpose of this research is to find out the effect vocabulary mastery toward student’s speaking skill, to find out the effect debating technique toward student’s speaking skill, to find out the effect vocabulary mastery and debating technique toward student’s speaking skill. This research has done of first semester students STKIP Kusuma Negara Jakarta by using the experimental research method. Sample of 60 students first semester which as chosen by random sampling using purposive sampling to choose the place of research experimental and control class and systematic sampling to decide member of sample and class for research. Data collective done by giving test for debating technique and speaking skill also giving questionnaire for vocabulary. The research of instrument has tested and tried by the validity and the reliability test used the program of SPSS. The data was analysis by using 2 way analysis of variance (ANOVA), Before doing the analysis the data normality was tested by using Kolmogorf-Smirnov test to see if the population where the sample was taken had normal distribution. The next analysis is to test the data homogeneity by using levenu’s test, to see if the population was derived from homogeneous population. The result of this research concluded: 1). Vocabulary gave the significant effect to the student’s speaking skill. Test result obtained that p-value for category vocabulary is 0.000 (<0.05). 2). Debating technique gave the significant effect to the student’s speaking skill. Test result obtained that p-value for debating technique 0.000 (<0.05). 3). There is interaction effect between vocabulary mastery and debating technique towards student’s speaking skill. Test result retrieved that p-value for category of vocabulary and debating technique is 0.000 (<0.05). Keywords: Vocabulary mastery, Debating Technique, Speaking Skill